Design and evaluation of a Fischer-Tropsch process for the production of waxes from biogas. (1st August 2017) - Herz, Gregor; Reichelt, Erik; Jahn, Matthias
Abstract: A process for the production of Fischer-Tropsch waxes from biogas is proposed. It is shown that the specific composition of biogas allows the production of syngas suitable for Fischer-Tropsch synthesis in one process step. The absence of an additional reverse water-gas shift reaction step simplifies the process concept, which is advantageous for the targeted application. For two reforming concepts, steam reforming and autothermal reforming, the process efficiency is calculated with help of a process model. The results show, that especially the concept based on steam reforming offers a high energetic efficiency of ηen  > 0.5. An economic feasibility study reveals advantages in comparison to state-of-the-art biogas CHP. For existing biogas plants the developed process concept offers a promising alternative for profitable operation. The process modeling results also show that the technical realization depends on the availability of advantageous inexpensive novel reactor concepts that are specifically developed for small-scale decentralized applications. Highlights: A process for the production of waxes from biogas is proposed. Energetic efficiencies >55% can be reached with the process. Economic feasibility of the concept was compared to biogas CHP. The production of valuable products from biogas is a promising concept.